Electoral Integrity: How Gerrymandering Matters. (3rd July 2017) - Kennedy, Sheila Suess
Abstract : Gerrymandering (partisan redistricting) is widely believed to deprive citizens of meaningful participation in the democratic process. It is seen as an obvious conflict of interest because there is ample evidence that lawmakers use redistricting to protect both their personal electoral prospects and their party's legislative advantages. The impression that an inherent conflict of interest occurs when legislators determine the composition of the population that will vote for them has revived efforts to reform the ways states handle redistricting and reignited scholarly disputes over the degree to which the ills ascribed to partisan redistricting are accurate. The U.S. Supreme Court is poised to revisit its redistricting jurisprudence, making it timely to revisit the contending academic arguments about the political effects of gerrymandering and the existing constitutional jurisprudence.